Nonpolar Liquid Lubricant Submerged Triboelectric Nanogenerator for Current Amplification via Direct Electron Flow. Issue 25 (13th May 2021) - Chung, Seh‐Hoon; Chung, Jihoon; Song, Myunghwan; Kim, Seonwoo; Shin, Dongjun; Lin, Zong‐Hong; Koo, Bonwook; Kim, Dongseob; Hong, Jinkee; Lee, Sangmin
Abstract: Triboelectric nanogenerators (TENGs) can convert a mechanical energy input to an electric energy output through Maxwell's displacement current. By increasing the electrical output and overcoming the mechanical limitations of TENGs, such devices can be used as an auxiliary power source for portable electronics. Nevertheless, the generation mechanism and structure must be optimized to compensate for the electrical and mechanical limitations of TENGs. This paper reports on a nonpolar liquid lubricant submerged TENG (LLS‐TENG), which can overcome the existing electrical and mechanical limitations of the TENG. When a nonpolar liquid lubricant is filled in the LLS‐TENG, the air breakdown can be effectively blocked owing to the large Debye length of such lubricants. In addition, the rolling friction and lubrication present in the LLS‐TENG can significantly reduce the friction wear of the device. Consequently, the LLS‐TENG can charge a commercial capacitor and battery by generating a high voltage and current output of up to 200 V and 170 mA, respectively. Abstract : This paper reports a nonpolar liquid lubricant submerged triboelectric nanogenerator that can effectively amplify current output and reduce friction wear by filling with a nonpolar liquid lubricant and utilizing rolling electrodes. Thanks to the large Debye length of the nonpolar liquid lubricant, the device can generate high electrical output under low rotational input.